2015
DOI: 10.1016/j.seppur.2014.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Se(IV) and Se(VI) from drinking water by coagulation

Abstract: a b s t r a c t Selenium (Se) is one of contaminants required to be regulated during drinking water treatment, however, little information has been collected to date regarding Se removal by coagulation. In this study, the performance of Se removal by coagulation has been evaluated with respect to the dependence on Se species, coagulant type, water pH and interfering ions. The results showed that a Fe-based coagulant was much more efficient than Al-based coagulants in Se removal. The removal of selenite (Se(IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…For example, the removal of <![CDATAfalse[AsO43-false]]> was achieved from 68.90% to 93.60% with the SCD values of PDADMAC increasing. The valence of anion pollutants also affected the flocculation process (Bellu et al., ; Hu et al., ). The flocculation efficiencies of high valence anionic pollutants (<![CDATAfalse[AsO43-false]]> and <![CDATAfalse[Fefalse(CNfalse)63-false]]>) were lower than that of low valence anionic pollutants (<![CDATAfalse[VO3-false]]>, <![CDATAfalse[MoO42-false]]>, and <![CDATAfalse[WO42-false]]>) by PDADMAC with the same SCD value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the removal of <![CDATAfalse[AsO43-false]]> was achieved from 68.90% to 93.60% with the SCD values of PDADMAC increasing. The valence of anion pollutants also affected the flocculation process (Bellu et al., ; Hu et al., ). The flocculation efficiencies of high valence anionic pollutants (<![CDATAfalse[AsO43-false]]> and <![CDATAfalse[Fefalse(CNfalse)63-false]]>) were lower than that of low valence anionic pollutants (<![CDATAfalse[VO3-false]]>, <![CDATAfalse[MoO42-false]]>, and <![CDATAfalse[WO42-false]]>) by PDADMAC with the same SCD value.…”
Section: Resultsmentioning
confidence: 99%
“…Coagulation/flocculation is widely applied in drinking water and wastewater treatment process for its simple and low-cost advantages (Fu & Wang, 2011;Hu, Chen, Chen, Liu, & Qu, 2015). Ionic polymers are often selected as organic flocculants because of their good water solubility, low dosage, and high charge density, such as polydimethyldiallyl ammonium chloride (PDADMAC) and cationic polyacrylamide (CPAM; Bolto, Dixon, Eldridge, & King, 2001;Casellassalha, Acobas, Bontoux, & Moreaud, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research has focused on low (acidic) pH values and high selenium concentrations like those encountered in industrial wastewaters rather than potable water [17]. Research on drinking water treatment mostly incorporates the use of relatively low-cost ferric or aluminum salts for the coagulation/precipitation process [19,20]. Hu et al (2015) showed that iron-based coagulant can reduce an initial selenium concentration of 250 µg/L by 98%, when a coagulant dosage of 0.4 mmol Fe 3+ /L) is applied in weakly acidic conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Research on drinking water treatment mostly incorporates the use of relatively low-cost ferric or aluminum salts for the coagulation/precipitation process [19,20]. Hu et al (2015) showed that iron-based coagulant can reduce an initial selenium concentration of 250 µg/L by 98%, when a coagulant dosage of 0.4 mmol Fe 3+ /L) is applied in weakly acidic conditions [19]. High coagulant dosages and acidic pH conditions were also reported as the crucial parameters that influence selenium coagulation by Adio et al (2017) when studying the precipitation of selenium by nZVI (nano zero-valent iron) [21].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum operating conditions were found to consist of an initial pH of 3.2, a current density of 250 A/m 2 , and an NaCL concentration of 1.5 g/L. About 84% total phenolic removal and 40% COD removal were achieved under optimal conditions Hu et al (2015b). investigated Se(IV) and Se(VI) removal from drinking water by coagulation.…”
mentioning
confidence: 99%